Research on the Digital Transformation of Corporate Finance in the Digital Economy Era (American Journal of Applied Statistics and Economics, 2025)
In the context of the digital economy, the digital transformation of corporate finance has become an irreversible trend. This article discusses the necessity, difficulties and innovative strategies of digital transformation of corporate finance. In view of the difficulties of digital transformation of corporate finance in the digital economy era, this article proposes innovative strategies such as strengthening guidance and thinking transformation, strengthening the construction of digital talent team, optimizing data integration application and risk control, and ensuring data governance is in place. These strategies are aimed at helping enterprises effectively respond to transformation challenges and improve financial management efficiency and competitiveness.